Karakteristik Fisik, Kimia, dan Fungsional Pati Ubi Banggai Asetat pada Berbagai Variasi Waktu Reaksi - If'all If'all; Asriani Hasanuddin; Abdul Rahim; Syahraeni Kadir (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
Banggai yam plant (endemic in Banggai Kepulauan Regency) is a potential raw material in production of modified starch. The one of techniques to increase the value of starch is modification of starch by acetylation method. This study objectives to determine the physical, chemical and functional characteristics of Banggai acetate yam starch at various reaction times. The study used a Completely Randomized Design with treatment time reaction (T), namely T1: 30 min, T2: 35 min, T3: 40 min, T4: 45 min, T5: 50 min, T6: 55 min. This study was conducted to determine the characteristics of yam acetate starch, which includes percent acetyl, degree of substitution, water and oil holding capacity (WHC/OHC), flammability, solubility, moisture content, ash, fat, protein, starch and amylose starch. The results showed that the longer reaction time under certain conditions will increase the acetyl percent, degree of substitution, WHC, OHC, flareability, solubility but reduce levels of fat, water, ash, fat, protein, starch and amylose starch, yam acetate. In this study at the best reaction time is (50 min), gives the acetyl percent 8.658% and substitution degree of 0.356, the value of WHC, OHC, Swelling ratio and solubility of 32.21%, 30.21%, 1.98 g/g, and 19.17% respectively.